Glide Path – An Ineluctable Route for Successful Endodontic Mechanics: A Literature Review - Mahima Bharat Mehta; Anupam Sharma; Aniket Jadhav; Aishwarya Handa; Abhijit Bajirao Jadhav; Ashwini A. Narayanan (Journal of International Clinical Dental Research Organization)
The glide path serves as the foundation for successful root canal therapy by facilitating effective instrumentation, disinfection, and subsequent obturation. It reiterates the importance of meticulous technique and need for attention to detail during endodontic treatment so as to avoid endodontic mishaps. Establishing a glide path creates a smooth and natural pathway which facilitates easy movement of files and reduces the likelihood of procedural errors. It also ensures an inviolate patency to the apical third of the root canal, allowing for the unimpeded passage of instruments and irrigants to the apex of the tooth ensuring disinfection of the critical zone of the root canal system. By gradually enlarging the canal space, a glide path helps to reduce torsional stress on the instruments, which further reduces the risk of instrument fracture. Clinicians should be familiar with various glide path preparation techniques and the use of specialized nickel–titanium files to achieve optimal results for root canal instrumentation. The aim of this review is to highlight the importance of glide path, techniques, and instruments that aid in easy establishment of it and probable negative impact of its absence when rendering root canal treatment.